2011
DOI: 10.1007/s00701-011-0945-1
|View full text |Cite
|
Sign up to set email alerts
|

Axonal regeneration effects of Wnt3a-secreting fibroblast transplantation in spinal cord-injured rats

Abstract: These results strongly suggest that transplanted Wnt3a secreting fibroblasts promote axonal regeneration and functional improvement after SCI. Although further investigation will be necessary to clarify the intracellular mechanism by which Wnt signaling promotes axonal regeneration and functional improvement, this approach could be a highly promising therapeutic strategy for SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…While some axons are likely absent due to the loss of neurogenesis at the injury site, the magnitude of the effect we observe suggests that axons from more distant surviving neurons may fail to regrow as well. Along with other studies (Park et al, 2013; Suh et al, 2011), our data suggest that Wnt/ß-catenin signaling may promote axon regrowth either directly, or through induction of secondary pathways in radial glia.…”
Section: Resultssupporting
confidence: 87%
“…While some axons are likely absent due to the loss of neurogenesis at the injury site, the magnitude of the effect we observe suggests that axons from more distant surviving neurons may fail to regrow as well. Along with other studies (Park et al, 2013; Suh et al, 2011), our data suggest that Wnt/ß-catenin signaling may promote axon regrowth either directly, or through induction of secondary pathways in radial glia.…”
Section: Resultssupporting
confidence: 87%
“…82,83 After SCI, Wnt5a is induced in reactive astrocytes surrounding the damaged area, and corticospinal axonal growth is inhibited by noncanonical activation of the Ryk receptor in both mice 28 and rats. 20 Consistently, inhibition of noncanonical Ryk activation using Ab 20,28 or, alternatively, activation of canonical Wnt signaling using either lithium, 84,85 exogenous Wnt3a administration, 79 or transplantation of Wnt3a-secreting fibroblasts 86 improves locomotor recovery by promoting axonal regeneration after SCI. In our study, we observed detectable levels of Wnt5a at the nonlesioned and all of the times we analyzed postinjury, and we observed an increase in the expression of Ryk during late time points.…”
Section: Discussionmentioning
confidence: 92%
“…The Wnt protein specifically binds to the N-terminal cysteine-rich region of the Frizzled (Fz) receptor and functions through the classical Wnt/β-catenin pathway as well as non-classical Wnt/PCP or Wnt/Ca pathway (2,34,35). Studies have shown that Wnt signaling abnormalities might be related to axonal injury after aplastic failure and the occurrence of certain mental diseases (3638). In a chronic pain model induced by multiple sclerosis, Wnt expression was upregulated in the spinal dorsal horn, which caused disease progression (39).…”
Section: Discussionmentioning
confidence: 99%